Loss Minimization of Power Distribution Network using Different Types of Distributed Generation Unit - Su Hlaing Win; Pyone Lai Swe (Institute of Advanced Engineering and Science, 2015)
A Radial Distribution network is important in power system area because of its simple design and reduced cost. Reduction of system losses and improvement of voltage profile is one of the key aspects in power system operation. Distributed generators are beneficial in reducing losses effectively in distribution systems as compared to other methods of loss reduction. Sizing and location of DG sources places an important role in reducing losses in distribution network. Four types of DG are considered in this paper with one DG installed for minimize the total real and reactive power losses. The objective of this methodology is to calculate size and to identify the corresponding optimum location for DG placement for minimizing the total real and reactive power losses and to improve voltage profile in primary distribution system. It can obtain maximum loss reduction for each of four types of optimally placed DGs. Optimal sizing of Distributed Generation can be calculated using exact loss formula and an efficient approach is used to determine the optimum location for Distributed Generation Placement. To demonstrate the performance of the proposed approach 36-bus radial distribution system in Belin Substation in Myanmar was tested and validated with different sizes and the result was discussed.